THE INFLUENCE OF ORGANIZATIONAL COMMITMENT, CAREER DEVELOPMENT AND WORK ENVIRONMENT ON EMPLOYEES’ JOB SATISFACTION (CASE STUDY AT PT. MAP SURVEILLANCES) - Wulan Istia Fatmawati; Chaerudin Chaerudin (Dinasti Publisher, 2021)
This research aims to learn further regarding the impact caused by Organizational Commitment, Career Development and Work Environment on Employee Job Satisfaction either partially or simultaneously. The research population amounted to 140 respondents with a sample filtered of 95 respondents who were employees at Head Office and Site Office of PT. Map Surveillances. The quantitative descriptive research method used multiple linear regression analysis through the version 22 SPSS (Statistical Package for the Social) application program. The results showed that Organizational Commitment, Career Development and Work Environment had a positive and significant impact on Job Satisfaction both partially and simultaneously.